The Influence Of Maternal Assistance On The Behavior And Dental Hygiene Status Of Children at SDN 2 Lamcot, Aceh Besar Regency - reca, reca; Mufizarni, Mufizarni; Nurasikin, Cut Aja; Salfiadi, Teuku (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Parents has an important role as a companion in child health care , because there are still many parents who think that baby teeth are only temporary and will be replaced by permanent teeth so they don't pay attention to the cleanliness of baby teeth . Study This aim For know influence accompaniment Mother to hygiene behavior and status tooth child in SDN 2 Lambcot Aceh Besar . This type of research is Quasi Experimental Design with an equivalent research design control group design with pre test and post test . The subjects in this study were all Class V students at SDN 2 Lamcot , Aceh Besar District totaling 60 children, then divided into two groups, the intervention group consisting of 30 children were given interventions (dental health education counseling and teaching students how to brush their teeth by accompanied by their parents ) whereas in the control group consisted of 30 children who were given interventions ( dental health education counseling and teaching students how to brush their teeth). The sampling technique in this study is the total population. The measuring instrument used is questionnaires and tools diagnosis . Analysis of the results of quantitative data in this study using Paired Sample T- Test and Independent Sample T- test . Data analysis used the Statistics Program for Social Science (SPSS), with hypothesis testing based on a significant level of p <0.05. The research results show that no _ there are differences in the level of knowledge, attitudes, actions and hygiene status teeth and mouth students before and after intervention statistically significant (p > 0.05) p exist group control . There are differences in the level of knowledge, attitudes, actions and hygiene status teeth and mouth students before and after intervention statistically significant (p < 0.05) p exist group treatment . There are differences in the values of knowledge, attitudes, actions, and hygiene status pupil teeth in both groups between groups treatment with control group p This shown statistically p<0.05) . Director recommends n to Mother For given education and information to parents and children regarding the importance of maintaining oral hygiene.